STUDI KEPEMIMPINAN DIGITAL DAN KEPEMIMPINAN KREATIF YANG MEMPENGARUHI INOVASI DI UMKM JATIMULYA BEKASI JAWA BARAT - Nining Widya Lestari (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2020)
The purpose of this research is to study the components of digital leadership and creative leadership that affect innovation in 10 SME companies in Bekasi, West Java. By using 90 saturated samples and PLS analysis. The results of the findings of this study are a significant influence between digital leadership and creative leadership on innovation both partially and simultaneously. Thus the management of SMEs must ensure that the process of creating a digital vision, communicating digital vision, implementing digital vision is a must in facing the technological changes of the 21st century. On the other hand, management must also ensure that the process of creating a creative leadership dimension in imagination, constructing a vision is a guarantor for the formation of levels. innovation in radical extremes.